MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN REFLEK TENTARA PADA ANAK USIA 4-5 TAHUN DI TK Q AL-MA’RUF KECAMATAN TAMPAN KOTA PEKANBARU - Azprima, Jeli; Chairilsyah, Daviq; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the gross motor ability of children who are still relatively low, this is evidenced from 1) the existence of some children who are less able to do walking activities on the board with the equilibrium balance, 2) some children are less able to throw in a directional and jump pad apupun pedestal appropriately. As for the purpose in this penelitin is to know the game reflex army can improve the abusive motor skills of children aged 4-5 years in kindergarten Q Al-Ma'ruf Tampan Sub-district Pekanbaru City. The type of this research is Classroom Action Research with subject number of 16 children. Technique of collecting data using observation technique. Data analysis in this research is by using formula percentage. Based on the results of the study showed that the motor abilities of children before the cycle or pre cycle cycle reached an average of 42.38 with the category began to develop (MB), whereas in cycle I the abusive motor ability of children increased to 64.13 with BSH category, pre cycles to cycle 1 reached 51%, then the classroom action performed on cycle II rough motor abilities increased better to 74.05 with BSB category, and the increase from pre cycle to cycle II reached 76% percentage. With this result shows that the arts reflex game can improve the gross motor skills of children aged 4-5 years in kindergarten Q Al-Ma'ruf Pekanbaru.Keywords : Ability, Crude Motoric, Reflective Game of the Army